Situação-problema: representações de acadêmicos do curso de Licenciatura em Matemática da UFSM - Pagliarini, Thaís Ribeiro (2007)
Although the term problem is greatly present in the daily routine of people who work with Mathematics, we can perceive, even nowadays, that its use is not always followed by a conscious understanding about its meaning. Taking this point into consideration, this research, which is linked to the UFSM Education Post-Graduation Program, introduced at the research area Curriculum, Teaching and School Practices, aims at studying UFSM Mathematics Degree Course undergraduate students representations about Problemsituations, as well as to investigate such representations having in mind the undergraduate formative way and the signals of the topic in the prescriptive to their future teaching practice. The methodology has a quantitative and qualitative character, happening in two different moments. At first, we will show percent data of the answers obtained, after that we will analyze from the elaborated categories, such as (1) the understanding about the Problemsituations by the Mathematics undergraduate students; (2) the Mathematics undergraduate students formation in their Mathematics Degree Course in terms of Problem-situations; (3) the importance given by the Mathematics undergraduate students to the Problem-situations; (4) types of Problem-situations solved by the Mathematics undergraduate students and (5) the feasibility seen by the undergraduate students in working with Problem-situations at schools. It is from this organization that we present the undergraduate students perceptions and the research results. Using the five categories, in order to make a cross-answer given as a theoretical reference, observing that the public politics and the implementation of suggestions proposed for them were out of all proportion, as well as the lack of knowledge from the academics about the problem-situations dynamics